N, H and C-atoms Concentrations in Flowing Afterglows of Microwave R/N\(_2\)-H\(_2\) and R/N\(_2\)-CH\(_4\) Discharges with R=N\(_2\), He, Ar and Their Applications to TiO\(_2\) Surface Nitriding - André Ricard; Jayr Amorim; Moustapha Abdeladim; Jean-Philippe Sarrette; Yu-Kwon Kim (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
Flowing afterglow plasmas have found their interest in soft surface treatments of sensitive materials in life science as the sterilization of medical instruments. Variations of N,H and C-atoms density has been determined along the reduced pressure flowing afterglows of microwave R/N2-H2 and R/N2-CH4 discharges with R=N2, He and Ar. Density of H and C-atoms and other nitrogen-active species such as N2(A), N2(X,v>13),N2+,NH,N(2D), CN were obtained from that of N-atoms calibrated by NO titration, using the method of band intensity ratios in several conditions (between early and late afterglows). It has been obtained the density of O-atoms and NO molecules coming from air impurities. It has been deduced the wall destruction probability of H,O and C-atoms on the quartz afterglow tube: \(γ\)HR,N2=10-3,\(γ\)oR,N2=(0.4-1) 10-3 and \(γ_C^N2\)=(0.7)10-3. The effects of H and C-atoms on N-atoms inclusion inside TiO2 surfaces are reported.